2015
DOI: 10.5430/ijba.v6n5p13
|View full text |Cite
|
Sign up to set email alerts
|

Leisure from International Voices: Foreign Labors’ Leisure Opportunities in Taiwan

Abstract: This research makes an attempt to explore whether or not sufficient public recreational facilities have been provided for foreign women workers in Taiwan and whether or not the general atmosphere makes them afraid to partake in leisure activities. The aim is to apply gender studies in order to understand the different perspectives that foreign female workers have of leisure experience, to explore the social structure and stereotypes which form the power to oppress women and to search for a way to eliminate suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Tsai [85] focused on female blue-collar foreign workers and examined their leisure activities after work in Taiwan, observing that their leisure activities were affected by their countries or origin and their work arrangements. Furthermore, Tsai [86] also discussed foreign white-collar workers' leisure opportunities in Taiwan and showed that most respondents regularly participated in leisure or sports activities after work.…”
Section: Tourism Behavior For Foreign Workers and A Given Groupmentioning
confidence: 99%
“…Tsai [85] focused on female blue-collar foreign workers and examined their leisure activities after work in Taiwan, observing that their leisure activities were affected by their countries or origin and their work arrangements. Furthermore, Tsai [86] also discussed foreign white-collar workers' leisure opportunities in Taiwan and showed that most respondents regularly participated in leisure or sports activities after work.…”
Section: Tourism Behavior For Foreign Workers and A Given Groupmentioning
confidence: 99%